An Analysis of English Pronunciation Training Applications for Elementary School Students: Google Pronouncation, Duolingo, and Cake - Nadia Tiara Antik Sari; Pani Herlina; Delia Apriliani; Ica Nurlaela; Andhini Oktafrina; Resa Azahra; Gilang Rajasa; Liptia Venica (CV. Creative Tugu Pena, 2025)
Digital learning is rapidly evolving and is increasingly recognized as essential, as it demonstrates adaptability in an era of rapid technological advancement. One area significantly influenced by this development is English education, which has benefited from various learning software and applications targeting the four core language skills: Listening, Speaking, Reading, and Writing. Among these, mastering speaking skills is crucial in English language learning. However, many students struggle with pronunciation. Engaging and interactive learning media can boost both motivation and learning outcomes. This study is a descriptive qualitative analysis that examines existing digital tools designed to support the development of speaking skills. Using content analysis, the study explores the use of Google Pronunciation, Duolingo, and Cake in teaching English speaking skills to elementary students. These applications provide interactive features and wide accessibility, allowing students to improve their pronunciation and speaking skills independently and in an enjoyable manner. Although these tools share the common goal of supporting English language learning, each has unique strengths and limitations depending on its features and platform. The findings suggest that these technologies can streamline the learning process and significantly enhance student outcomes, making English speaking practice more effective and enjoyable. This study offers an overview of how these digital tools contribute to the improvement of speaking skills among elementary school students.